Optimal performance characteristics of a two-stage irreversible combined refrigeration system under maximum cooling load per unit total cost conditions - Sahin, B; Kodal, A; Koyun, A (PERGAMON-ELSEVIER SCIENCE LTD, 2001)
In this payer, we report a study on the thermoeconomical performance optimization of a two-stage irreversible combined refrigeration system affected by the irreversibility of heat transfer across finite temperature differences, the heat leak loss between the external heat reservoirs and the internal dissipation of the working fluids. The cooling load per unit total cost is taken as an objective function for the optimization, The maximum of the objective function and the corresponding optimal performance and design parameters have been derived analytically. The global and the optimal performance characteristics curves are presented in terms of technical and economical parameters. The effects of the major irreversibilities and the economical parameters on the general and optimal performances have been investigated. Some new results, which may play an important role in determining the economical design conditions of real two-stage refrigeration systems, are obtained. (C) 2000 Elsevier Science Ltd. All rights reserved.
Keywords: finite time thermodynamics; thermoeconomic optimization; irreversible combined refrigerator; ENDOREVERSIBLE CARNOT REFRIGERATOR; HEAT-PUMPS; OPTIMIZATION; COEFFICIENT; CYCLES; Thermodynamics; Energy & Fuels; Mechanics